2009 Sixth International Conference on Fuzzy Systems and Knowledge Discovery 2009
DOI: 10.1109/fskd.2009.494
|View full text |Cite
|
Sign up to set email alerts
|

Effluent Quality Prediction of Wastewater Treatment Plant Based on Fuzzy-Rough Sets and Artificial Neural Networks

Abstract: Effluent ammonia-nitrogen (NH3),chemical oxygen demand (COD) and total nitrogen (TN) removals are the most common environmental and process performance indicator for all types of wastewater treatment plants (WWTPs). In this paper, a soft computing approach based on the back propagation (BP) neural networks and fuzzy-rough sets (FR-BP) has been applied for forecasting effluent NH3-N, COD and TN concentration of a real WWTP, in which the fuzzy-rough sets theory is employed to perform input selection of neural ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…e sharp fluctuation of TN and COD cannot be ignored for this issue. For example, effluent COD mostly fluctuated within 10 to 60 mg/L in the study of Luo et al [23]. In contrast, the range is magnified to 3-335 mg/L in this study.…”
Section: Advantages Limitations and Recommendation For Futurecontrasting
confidence: 65%
See 1 more Smart Citation
“…e sharp fluctuation of TN and COD cannot be ignored for this issue. For example, effluent COD mostly fluctuated within 10 to 60 mg/L in the study of Luo et al [23]. In contrast, the range is magnified to 3-335 mg/L in this study.…”
Section: Advantages Limitations and Recommendation For Futurecontrasting
confidence: 65%
“…(2) Inputs contained some parameters that are difficult or costly to be measured. In some cases, influent TN even served as inputs for effluent TN prediction [23].…”
Section: Limitations Of Current Cases Applied On Modelling Thementioning
confidence: 99%
“…Guan et al and Wang et al proposed the soft-sensing method for predicting the quality parameters of wastewater treatment [23,24]. Luo et al developed a soft computing approach based on the back propagation neural networks and fuzzy-rough sets to predict effluent NH 3 -N, COD, and total nitrogen (TN) concentration of a real WWTP [25]. The results showed that the prediction by this approach was better than the other traditional modeling approaches.…”
Section: Introductionmentioning
confidence: 99%